Comparison of microleakage of Scotchbond™ Universal Adhesive with methacrylate resin in Class V restorations by two methods: Swept source optical coherence tomography and dye penetration - Hamid Kermanshah; Hossein Khorsandian (Wolters Kluwer Medknow Publications, 2017)
Background: One of the most important factors in restoration failure is microleakage at the restoration interface. Furthermore, a new generation of bonding, Scotchbond Universal (multi-mode adhesive), has been introduced to facilitate the bonding steps. The aim of this study was to compare the microleakage of Class V cavities restored using Scotchbond™ Universal with Scotchbond Multi-Purpose in two procedures. Materials and Methods: Eighteen freshly extracted human molars were used in this study. Thirty-six standardized Class V cavities were prepared on the buccal and lingual surfaces. The teeth were divided into three groups: (1) Group A: Scotchbond Universal with "self-etching" procedure and nanohybrid composite Filtek Z350. (2) Group B: Scotchbond Universal with "total etching" procedure and Filtek Z350. (3) Group C: Scotchbond Multi-Purpose and Filtek Z350. Microleakage at enamel and dentinal margins was evaluated after thermocycling under 5000 cycles by two methods of microleakage assay: swept source optical coherence tomography (OCT) and dye penetration. Wilcoxon's signed-rank test and Kruskal-Wallis test were used to analyze microleakage. Results: In silver nitrate dye penetration method, group A exhibited the minimum microleakage at dentin margins and group C exhibited the minimum microleakage at enamel margins (P < 0.05). Furthermore, in OCT method, group C demonstrated the minimum microleakage at enamel margins (P = 0.047), with no difference in the microleakage rate at dentin margins. Conclusion: Scotchbond Universal with "self-etching" procedure at dentin margin exhibited more acceptable performance compared to the Scotchbond Multi-Purpose with the two methods.